EFEKTIFITAS JUS TERUNG BELANDA TERHADAP PENINGKATAN KADAR HEMOGLOBIN PADA IBU HAMIL DENGAN ANEMIA - Andriyani, Fitri "; Utami, Gamya Tri; Dewi, Yulia Irvani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract Pregnant women are susceptible to anemia. Prevention of anemia in pregnant women besides drink Fe tablets, other therapies give terung belanda (Solanum Betaceum) juice. The aim of this research was analized the effectiveness of terung belanda (Solanum Betaceum) juice therapy towards elevated levels of hemoglobin for pregnant women with anemia. A quasy experimental study was used in this study which was performed in Public Healts Centre Sail, using purposive sampling technique. The study was carried out towards 30 pregnant women who had anemia (15 respondents as a treatment group and 15 respondents as a control group) and with inclusion criteria for the study. An instrument and easy touch digital levels of hemoglobin were used to collect the data. Data analyzed into univariate and bivariate by independent and dependent sample t test. The results showed that therapy terung belanda juice was effective towards elevated levels of hemoglobin  for pregnant women with anemia (p value 0.008). The results of this research is  recommended to healths care to give education and promotion about complementary therapy for pregnant women to prevent anemia with terung belanda (Solanum Betaceum) therapy juice. Keywords: anemia, hemoglobin levels, pregnant women, terung belanda juice.